Maternal Identity, Grief, and Creative Subjectivity in Niño y sombras by Concha Méndez - Green-Nagle, Beth A. (My University, 2016)
The poetry of Concha Mendez reflects the human condition, particularly motherhood and grief in a Spanish context. This dissertation examines the embodied, relational, dynamic, and adaptable maternal identity; the mother’s grief process in response to perinatal death; and creative subjectivity in the twenty-eight poems that form Niño y sombras by Concha Méndez. This analysis draws from Christine Battersby’s The Phenomenal Woman, a seminal work of feminist philosophy. Explored from a matrifocal perspective, insight is gained into the expression of Mendez’s maternal identity, how the stillbirth of her son and her subsequent grief process impacted that maternal identity, and finally how Méndez affirmed herself as creative subject, using poetry to create meaning and communicate her maternal experience. Bereft of more formal mourning rituals, Mendez recorded her memories, experiences, and grief surrounding the loss of her son in the poems of Niño y sombras. Méndez composed these memories in a poetic ritual to recognize the significance of her child, his death, and her own heartache. In addition, the analysis of the poems provides insight into early twentieth-century Spanish women’s lived experiences of motherhood and grief.
Keywords: Concha Méndez; Maternal Identity; Grief; Subjectivity; Infant death; Spanish poetry; Niño y sombras; Elegy; Stillbirth; Embodiment